2008
DOI: 10.1111/j.1752-4598.2008.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing impacts on moth diversity and abundance on a Scottish upland estate

Abstract: Abstract.  Livestock grazing is the most important direct management impact on grasslands in upland areas of the UK. For phytophagous species, such as Lepidoptera, the impact is primarily through grazing altering the species composition and structure of the vegetation. However, specific impacts related to different grazing regimes are not well understood for this group of insects. Within a replicated controlled grazing experiment, nocturnal adult moths were sampled by light trapping in the fifth year after es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 39 publications
(46 reference statements)
3
31
0
Order By: Relevance
“…3). This is related to the unexpected outcome of our first hypothesis but is a logical result as the abundance and biomass of foliar arthropods decreased significantly with decreasing vegetation height, as shown by other studies (Britschgi, Spaar, & Arlettaz 2006;Dennis et al 2008;Kruess & Tscharntke 2002;Littlewood 2008). However, foraging squares did tend to contain more invertebrate biomass than random squares at the preferred vegetation characteristics, i.e.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…3). This is related to the unexpected outcome of our first hypothesis but is a logical result as the abundance and biomass of foliar arthropods decreased significantly with decreasing vegetation height, as shown by other studies (Britschgi, Spaar, & Arlettaz 2006;Dennis et al 2008;Kruess & Tscharntke 2002;Littlewood 2008). However, foraging squares did tend to contain more invertebrate biomass than random squares at the preferred vegetation characteristics, i.e.…”
Section: Discussionmentioning
confidence: 48%
“…This system has been used to explore linkages between grazing management, sward structure, plant composition, invertebrate abundance and foraging site selection of a common insectivorous passerine, the meadow pipit (Anthus pratensis L.). The livestock grazing treatments have initiated changes, and hence differences, in vegetation structure rather than plant species composition (R. Pakeman, unpublished data) and in the abundance and biomass of invertebrates (Dennis et al 2008;Littlewood 2008). The experiment has also demonstrated that the egg size (Evans, Redpath, Evans, Elston, & Dennis 2005) and breeding abundance (Evans et al 2006) of meadow pipits was positively affected by a low intensity, mixed grazing regime compared to sheep grazing at the same or higher intensity.…”
Section: Introductionmentioning
confidence: 73%
“…In southern Sweden, there were fewer butterfly species in sheep-grazed than in abandoned seminatural grasslands, which was seen as the indirect effect of sheep selectivity for flowering plants (Ö ckinger et al, 2006). High-intensity sheep grazing with 2.7 sheep per ha also produced the lowest moth abundance and species richness in an upland acid grassland; moths peaked in abandoned plots and at a low grazing intensity of 0.9 sheep per ha (Littlewood, 2008). Conversely, bumblebee species richness and abundance were higher in sheep-grazed than in unmanaged grasslands (Carvell, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…We assess the moths' response to two contrasting regimes, mowing and abandonment, within a middle-sized fenland reserve. Unlike studies restricted to Macrolepidoptera, or macro-moths (e.g., Woiwod & Hanski 1992;Grand & Mello 2004;Littlewood 2008;Mutshinda et al 2008;Merckx et al 2009a, b), we also included Microlepidoptera (micro-moths), which are more difficult for handling and identification and hence rarely considered in ecology studies (but see Fuentes-Montemayor et al 2011;Summerville et al 2001). We expected that due to small body sizes, Microlepidoptera might contain a higher number of specialised sedentary species, and should be more sensitive to impacts of site management (e.g., Vávra et al 1996;Spitzer et al 1999;Šumpich 2006;Summerville et al 2007).…”
Section: J šUmpich and M Konvičkamentioning
confidence: 99%